Investigation of a Diesel Engine with Ceramic and platinum coated piston using Canola oil, Soyabean oil and Palm oil blended with Ethanol. (2017) - Yerrennagoudaru, Hiregoudar; Manjunatha, K.
Abstract: As we know that all over the world the diesel vehicle population is growing at an alarming rate. The emission will irritate skin, eyes, nose, and throat and also leads to bronchitis asthma in the long run and has been led to air pollution. It is a serious concern with the pollution point of view. Existing fissile fuel deposits may come for another 40 years and Costs of Fissile Fuels are day by day increasing. Emissions caused by these fissile fuels leads to air pollution. Developing Countries like India depends on its fissile fuel requirement on foreign countries for which spars huge forging currency in purchasing the crude oil, thus the inflation rate increases, rupees valve decreases hence the country economy and development decrease.Hance view of above drawbacks there is urgent need to find an alternative fuel in the existing engines. In view of increasing pressure on crude oil reserves and environmental degradation as an outcome, fuels like Alcohols and vegetable oils may present a sustainable solution as it can be produced from a wide range of plants and seeds. The present investigation evaluates Ethanol blended with canola oil, soyabean oil, plama oil in CI Engine. A Twin cylinder C I engine adapted to study the brake thermal efficiency, brake specific energy consumption, and emissions In this study, the diesel engine was tested using Diesel and Ethanol blended with canola oil, soyabean oil, plama oil. From this study the emissions like HC and CO, NOx, and Aldehydes has been reduced and Ehanol blended with vegetable oils are substitute to diesel fuel.